Pesquisas em Comunicação Suplementar e Alternativa na Educação Infantil - Massaro, Munique; Deliberato, Débora (Universidade Federal do Rio Grande do Sul - Faculdade de Educação, 2017)
Abstract: The aim of this study was to map the production of knowledge on Augmentative and Alternative Communication in Early Childhood Education indexed in scientific databases from 1980 to July 2015, and conference proceedings of the Brazilian Society for Augmentative and Alternative Communication. Eighty studies conducted both nationally and abroad, were found regarding the theme which is recent in the Brazilian panorama. Studies abroad focus on the development of language and communicative aspects of children with disabilities, while in Brazil the research intends to provide school support with activities and teaching strategies adapted through augmentative and alternative communication.

Resumo: O objetivo deste estudo foi mapear a produção de conhecimento acerca da Comunicação Suplementar e Alternativa na Educação Infantil indexada em Bases de Dados Científicos de 1980 a julho de 2015 e nos Anais do Congresso Brasileiro de Comunicação Alternativa. Foram encontrados 80 trabalhos nacionais e internacionais a respeito da temática. O tema é recente no panorama brasileiro. As pesquisas internacionais focalizaram o desenvolvimento da linguagem e aspectos comunicativos das crianças com deficiência e pesquisadores brasileiros se propuseram a dar suporte em escolas com adaptações de atividades e estratégias pedagógicas por meio da comunicação suplementar e alternativa.
Studies on Augmentative and Alternative Communication in Early Childhood Education
Keywords: Special Education; Early Childhood Education; Alternative and Augmentative Communication.; Educação Especial; Educação Infantil; Sistemas de Comunicação Alternativos e Suplementares